The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/1750-3841.16425
|View full text |Cite
|
Sign up to set email alerts
|

Getting hot: Effect of chili pepper addition on sensory perception of liquid and solid foods

Abstract: The impact of trigeminal oral burn and pungency on taste, flavor, and mouth-feel perception of commercially available foods is underexplored. This study aimed to determine the effect of oral burn sensations evoked by the addition of chili powder to tomato soup, beef burger patties, and curried rice on taste, flavor, and mouth-feel perception. Chili powder was added to tomato soups, beef burger patties, and curried rice at four concentrations. A consumer panel comprising n = 66 participants (49 women, 25.5 ± 5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Related to oral burn, reductions in taste, flavor, and mouthfeel intensity caused by oral burn might be more pronounced in liquid than in solid foods. This study demonstrated how trigeminal stimuli can be applied to modulate flavor and mouthfeel perception of foods (Lyu et al, 2023).…”
mentioning
confidence: 78%
“…Related to oral burn, reductions in taste, flavor, and mouthfeel intensity caused by oral burn might be more pronounced in liquid than in solid foods. This study demonstrated how trigeminal stimuli can be applied to modulate flavor and mouthfeel perception of foods (Lyu et al, 2023).…”
mentioning
confidence: 78%